AB0376 Retention Rates and Clinical Efficacy of Tocilizumab as First-Line Biologics Compared To Second-Line in Patients with Rheumatoid Arthritis. (15th July 2016) - Okano, T.; Inui, K.; Tada, M.; Sugioka, Y.; Mamoto, K.; Koike, T.; Nakamura, H.
Abstract : Background: To date, biologic disease-modifying anti-rheumatic drugs (bDMARDs) targeting cytokines such as tumor necrosis factor (TNF)-α or interleukin (IL)-6 have been established as a standard therapy for rheumatoid arthritis (RA) patients with insufficient responses to conventional synthetic DMARDs such as methotrexate (MTX). The IL-6 receptor blocking monoclonal antibody, tocilizumab, is included as one of the first-line bDMARD in the latest European League against Rheumatism (EULAR) recommendations [1]. However, there has been few data as the retention rates of tocilizumab. Objectives: This study aimed to investigate the retention rates and clinical efficacy of tocilizumab as first-line bDMARD compared with second-line treatment in patients with RA. Methods: This is a retrospective study. All RA patients who treated with tocilizumab were included this analysis. These patients were divided into two groups. In the first group, tocilizumab was used as a first-line bDMARDs (1st group). Patients in the other group received tocilizumab as a second-line or more treatment (2nd group). Retention rates and clinical efficacy assessed by disease activity score in 28 joints (DAS28; on the basis of the erythrocyte sedimentation rate, ESR) and clinical disease activity index (CDAI) from week 0 to week 52 were assessed. The discontinuation ratio of glucocorticoid and MTX was also evaluated. Moreover, the effect of tocilizumab for bone was assessed by bone mineral density (BMD) of lumber spine and hip, and bone metabolic marker (BMM) of urinary type I collagen cross-linked N-telopeptide (NTX) and bone-specific alkaline phosphatase (BAP). Results: Fifty-seven patients in 1st group and 75 patients in 2nd group were analyzed in this study. Retention ratio at week 24 and 52 was 94.7 and 80.7% in 1st group and 77.3 and 64.0% in 2nd group, respectively. Of 11 discontinued patients in 1st group, only 2 patients were withdrawal due to inadequate response. DAS28 remission rates were 17.4, 45.7, 50.0, 41.3 and 39.1% in 1st group and 8.3, 22.9, 29.2, 33.3 and 37.5% in 2nd group at week 4, 12, 24, 36 and 52, respectively. CDAI remission rates were 8.7, 10.9, 13.0, 23.9 and 15.2% in 1st group and 0, 6.3, 10.4, 14.6 and 10.4% in 2nd group at week 4, 12, 24, 36 and 52, respectively. The dose of MTX was reduced in 11 patients and MTX was withdrawal in 4 patients among 34 patients of 1st group using MTX at week 0. The dose of glucocorticoid was reduced in 16 patients and glucocorticoid was withdrawal in 10 patients among 20 patients of 1st group using glucocorticoid at week 0. BMM was not significantly changed and BMD was kept in both groups. Conclusions: High retention rates and clinical efficacy of tocilizumab as first-line biologic treatment was found in retrospective research. Moreover, dose reduction and withdrawal of MTX or glucocorticoid was achieved in some patients with tocilizumab. References: Smolen JS, Landewé R, Breedveld FC, Buch M, Burmester G, Dougados M, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis. 2014;73(3):492–509. Disclosure of Interest: None declared